A phase wise approach for fault identification. Issue 1 (2nd January 2018) - Kumar, Sushant; Ranjan, Prabhat
Abstract: Making software with high quality assurance is becoming difficult due to software testing and maintenance is costly and time consuming phases of software development life cycle (SDLC). This takes more than half the cost of software development. Researchers are already proposed methods to reduce the cost and time of software testing. However, these methods still not properly handle software testing process. The assurance of software quality is very crucial for any organizations so the cost of testing is increasing day by day. Therefore the scope of finding the fault from software is challenging task. However the evaluation of software quality at early stage is related to human centric and expert knowledge about the software. For this a phase wise fault identification approach using fuzzy inference system has proposed. This method finds the fault in every phase of the software based on fuzzy intuitive based approach. The fuzzy inference systems have applied with every phase to identify the fault. The resultant fault is used for the analysis of the software. This will provide sufficient time for developers, designers and tester to handle the fault in a given time frame. The work will help to increase the software quality.